Impact of Employer Branding on Employee Commitment: Employee Engagement as a Mediator - Aasia Yousf; Shabana Khurshid
Employer branding has fascinated human resources (HR) managers and establishments over the last two decades. This is attributed to its practical business implications and being a strong predictor of many favourable organizational outcomes. Due to the fierce business rivalry and market saturation in recent times, businesses are increasingly looking to engage their workforce in order to induce employer commitment among them. Employer brand is one factor that can help organizations keep their employees involved in the job. Employee engagement is critical for service brands, such as the banking industry, for delivering better customer service and maintaining a motivated workforce. An engaged workforce is also more committed towards the organization, which also leads to many desirable business outcomes. This study targeted 485 employees from two banks (one a public sector bank and the other a private bank), which resulted in 409 functional responses. The work objective was to examine the influence of employer brand on employee engagement, which may lead to organizational commitment. This article also examined the mediating role of employee engagement with respect to the five dimensions of employer brand and organizational commitment. The regression analysis using structural equation modelling (SEM) revealed that all five dimensions of employer brand influence employee engagement. Employee engagement also shares a positive and significant association with organizational commitment. Moreover, the mediation analysis also revealed that employee engagement partially mediates the relationship between employee engagement and organizational commitment. These study findings have important implications for business managers, HR managers and academicians.